Recurrent YAP1::MAML2 fusions in “nodular necrotizing” variants of myxoinflammatory fibroblastic sarcoma: a comprehensive study of 7 cases - Perret, Raul; Tallegas, Matthias; Velasco, Valérie; Soubeyran, Isabelle; Coindre, Jean-Michel; Azmani, Rihab; Baud, Jessica; Bacle, Guillaume; De Pinieux, Gonzague; Le Loarer, François (Modern pathology, 2022)
Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare soft tissue tumor with a predilection for the distal extremities and a tendency for local recurrence. Morphologically, MIFS consists of spindle and bizarre epithelioid cells resembling virocytes embedded in a fibrous to myxoid stroma with an abundant inflammatory infiltrate. Importantly, the molecular landscape of MIFS is wide and includes: VGLL3 amplification, BRAF fusion/amplification and OGA/TGFBR3 rearrangements. In this study, we describe a variant of MIFS showing a frequent nodular configuration associated with necrosis and recurrent YAP1::MAML2 fusions. The cohort consisted of 7 patients (4 females and 3 males) ranging in age from 21 to 71 years (median: 47 years). Two tumors (28%) occurred in acral locations while the remaining cases were more widely distributed (thigh, n = 2; arm, n = 1; neck; n = 1; chest-wall, n = 1). Tumor size ranged from 10 to 38 mm (median: 20 mm). Histologically, lesions frequently presented as nodules with central areas of necrosis, and were predominantly composed of sheets of epithelioid cells with large vesicular nuclei and prominent nucleoli (Reed-Sternberg-like cells or virocytes). The stroma was mostly fibrous and showed a polymorphous inflammatory infiltrate. Myxoid stromal changes were focally seen in one case, and pseudolipoblasts were absent. The immunophenotype was nonspecific, with only pan-keratin (AE1-AE3) and cyclin D1 expression in a subset of cases. RNA-Sequencing detected YAP1::MAML2 fusions in 3/7 cases; aCGH showed no significant gene copy number variations in 4 tested cases, and FISH analysis showed no VGLL3 amplification in 1 tested case. Follow-up was available for 6 cases, ranging from 7 to 63 months (median: 42 months). Local recurrence and metastasis were not seen and one tumor showed spontaneous regression following initial biopsy. In conclusion, we describe a novel variant of MIFS with distinctive clinicopathological and molecular features for which we propose the term “nodular necrotizing” MIFS.